OVERVIEW OF TUBERCULOSIS PREVENTIVE TREATMENT AMONG CHILDREN IN SURABAYA - Rizka Aprilidyawati; Chatarina Umbul Wahjuni; Rosita Dwi Yuliandari (Jurnal Berkala Epidemiologi, 2020)
Background: A high prevalence of tuberculosis (TB) infection rates is followed by high rates of TB infection in children. The TB Preventive Treatment (TPT) for children with Isoniazid (INH) is one of the primary activities to improve TB cases by finding them early to prevent the transmission of TB to children. Purpose: This study aimed to describe the implementation of TPT with prophylactic INH among children in Surabaya. Methods: This research was a descriptive observational study with a case series design using secondary data on the provision of TPT in children, child TB cases in Surabaya City in 2016–2018, and a network of partnerships with hospitals/clinics/doctors’ private practices for the prevention and control of TB in the city of Surabaya in 2016–2018 as the population. The data were collected by in-depth interviews with the holders of the TB prevention and control program of Surabaya. The data were analyzed by comparing and describing the targets and achievements of the INH administration in children. Results: The implementation of INH for children in Surabaya is not optimal and has not reached the targets. The networking of health facilities with providers for the provision of TPT with INH for children is still low in Surabaya City. Conclusions: Delivery of INH for children in Surabaya has been implemented and has increased, however, it is not optimal because it has not reached the targeted districts/municipalities that determined.